Does inward FDI crowd-out domestic investment? evidence from Uganda - Kasule, Twaha Ahmed; Mat Ghani, Gairuzazmi; Mohamad, Noorihsan; Mat Derus, Alias (2014)
This paper investigates the crowding-out effect of foreign direct investment on domestic investment in Uganda. The analysis examines the existence of this effect on the economy as a whole and at sectoral level for all the 9 production sectors, using data from 1992 to 2012. Our results reveal a robust, neutral effect on the aggregate economy. At the sectoral level, initial results suggest the existence of a crowding-out effect in four sectors, crowding-in effect in two sectors and a neutral effect in three sectors. But overall, the results are robust in only six sectors. Finally, our exogeneity test for the FDI variable illustrate that past growth rates included in the investment function do not influence inward FDI, implying that there is no endogeneity problem in our analysis.